AC magnetic field regulated in-vivo switch of Hf-substituted magnetite (HfxFe3−xO4,0.01 ≤ x ≤ 0.8) nanoparticles - Srivastava M.; Meena S.S.; Mandal R.K.; Yusuf S.M.; Prasad N.K. (My University, 2025)
We report the structural and magnetic behavior of HfxFe3−xO4(0.01 ≤ x ≤ 0.8) magnetic nanoparticles. Such studies are lacking in the literature. XRD patterns after Rietveld refinement for all the samples confirm the formation of single phase inverse spinel structure. The refined structure data suggests that Hf occupies only octahedral sites at lower concentration (x ≤ 0.2) but get distributed to tetrahedral sites for x ≥ 0.4 along with these. Accordingly, a continuous change in the lattice parameter was observed. The morphology of particles was nearly spherical and the size was found to be in the range of 10–30 nm. The electron diffraction patterns support formation of cubic spinel structure. X-ray photoelectron spectroscopy (XPS) studies suggest that the samples contain only Fe2+, Fe3+and Hf4+ions. The elemental mapping for Fe and Hf for the samples by electron probe micro analyzer (EPMA) also confirm their presence. The saturation magnetization (MS), remnant (Mr) and coercivity (HC) values were found to be 51.07 A m2/kg, 0.98 A m2/kg and 1.7 mT, respectively for x = 0.06. However, with increased Hf-concentration, a continuous decrease in the MSvalue was observed. The value of Mössbauer parameters like hyperfine field (BHF) and isomer shift (δ) conform the distribution of Hf cations at two aforesaid sites established by Rietveld analysis also. Co-existence of ferrimagnetic and superparamagnetic states was established by Mössbauer spectra as well as from the nature of hysteresis loop. Despite their higher magnetization values and their Curie temperature (TC) higher than 325 °C, almost all the samples displayed stabilization of temperature near 50 °C during hyperthermia experiment. The stabilization of temperature was found to be a function of concentration of Hf in Fe3O4as well as of the amplitude and frequency of the field. Such a stabilization of temperature near therapeutic temperature during magnetic hyperthermia is similar to that of our earlier observations for ZrxFe3-xO4(0.01 ≤ x ≤ 1.0) nanoparticles. © 2016 Elsevier B.V.